Evaluation of additional causes of hip pain in patients with femoroacetabular impingement syndrome - Gowd, Anirudh K.; Beck, Edward C.; Trammell, Amy P.; Edge, Carl; Stubbs, Allston J. (Frontiers in Surgery, 2022)
Femoroacetabular impingement syndrome (FAIS) is an increasingly prevalent pathology in young and active patients, that has contributing factors from both abnormal hip morphology as well as abnormal hip motion. Disease progression can be detrimental to patient quality of life in the short term, from limitations on sport and activity, as well as the long term through early onset of hip arthritis. However, several concurrent or contributing pathologies may exist that exacerbate hip pain and are not addressed by arthroscopic intervention of cam and pincer morphologies. Lumbopelvic stiffness, for instance, places increased stress on the hip to achieve necessary flexion. Alternatively, pseudoradiculopathy may be produced through direct impingement of nerves resulting in hip pain or numbness. Pathology at the pubic symphysis and sacroiliac joint may exist concurrently to FAIS through aberrant muscle forces. Additionally, both femoral and acetabular retro- or anteversion may contribute to impingement not associated with traditional cam/pincer lesions. Finally, microinstability of the hip from either osseous or capsuloligamentous pathology is increasingly being recognized as a source of hip pain. The present review investigates the pathophysiology and evaluation of alternate causes of hip pain in FAIS that must be evaluated to optimize patient outcomes.